Improving English Speaking Skills Using Creative Crafting Media - Kania Paswa Clearesta; Musiman, Musiman; Sih Pratiwi, Dyah (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study investigates the use of creative handicraft media to improve the English speaking skills of eighth-grade students at SMP Surya Dharma 2 Bandar Lampung. The research was conducted in response to students’ difficulties in speaking English, particularly related to low confidence, limited vocabulary, and fear of making mistakes. Handicraft activities were incorporated into speaking lessons to provide students with meaningful learning experiences and to encourage active participation. The results show that the use of creative handicraft media positively influences students’ speaking performance and classroom involvement. This study demonstrates that creative handicraft media can be an effective learning alternative in junior high school English classes, as it helps create a more engaging learning atmosphere and supports students in developing confidence when speaking English.